Methane hydrate formation in the presence of graphene oxide - Dr Diana Taylor; Dr Neal Skipper; Mr Matt Billing; Dr Tristan Youngs (ISIS Facility, 2015)
In this proposal we wish to study in situ formation of methane hydrates in the presence of graphene oxide. The aim of this research is to enable us to understand how different types of particle effect the occurrence and rate of methane hydrate nucleation. Recent simulations have predicted that in the presence of hydrophilic particles, methane, and therefore hydrate, should prefer the bulk to interfacial region. Neutrons and NIMROD are essential for this work, as they will allow us probe the relevant length and timescales, and also to exploit H/D labelling of the methane. In our previously awarded experiments RB1320495, RB1410533 and RB1400022, we successfully studied systems containing planar clay minerals and weakly hydrophilic nanosperes. In this experiment we will study nucleation in the presence of a more hydrophobic particle, namely graphene oxide.